2 NASAL CONTINUOUS POSITIVE AIRWAY PRESSURE DURING PROLONGED VENTILATION AFFECTS PULMONARY EXPRESSION OF STAT3 AND ITS DOWNSTREAM TARGET SOCS3 IN THE PREMATURE LUNG. Issue 1 (1st January 2007) - Wilkinson, B.; Metcalfe, D.; Callaway, C.; Dahl, M. J.; McKnight, R. A.; Lane, R. H.; Albertine, K. H.
Abstract : Objective: Chronic lung disease (CLD) of prematurity associated with mechanical ventilation (MV) is characterized in part by persistently thick, cellular mesenchyme. Power blot analysis of lung tissue revealed that STAT3 (signal transducers and activators of transcription 3) protein was significantly less in chronically ventilated preterm lambs managed by nasal continuous positive airway pressure (CPAP) compared with MV, suggesting dysregulation of cell proliferation with MV. We hypothesized that nasal CPAP management will result in less pulmonary mesenchymal cell proliferation and STAT3 expression and more SOCS3 (suppressors of cytokine signaling 3; negative feedback on STAT3) expression compared with MV management. Materials/Methods: Preterm lambs (≈132 days' gestation; term ≈148 days), treated with antenatal steroids and postnatal surfactant, were managed by either nasal CPAP or MV ( n = 4 each). The lungs were analyzed morphologically and biochemically. Results: Abundance of PCNA and STAT3 proteins was lower in the nasal CPAP group (1.1 ± 0.5 and 4.8 ± 1.0, respectively; mean ± SD) compared with the MV group (13.0 ± 3.2 and 7.9 ± 1.1, respectively; both p < .05). Conversely, SOCS3 protein abundance was greater in the nasal CPAP group (15.7 ± 2.9) compared with the MV group (8.8 ± 1.2; p < .05). Cellular localization of PCNA, STAT3, and SOCS3 proteins was in mesenchymal cells. Conclusion: Nasal CPAP permits alveolar formation in part by allowing appropriate expression of STAT3/SOCS3 proteins, such that cell proliferation is down-regulated among mesenchymal cells in the immature lung's parenchyma. HL62875, HL56401, HD41075, T35 HL07744, CHRC.